A 90-day oral toxicity study of glycolipids from Dacryopinax spathularia in Beagle dogs. (November 2017) - Bitzer, Jens; Henkel, Thomas; Nikiforov, Andrey I.; Rihner, Marisa O.; Henderson, Kim A.
Abstract: The subchronic toxicity of glycolipids from Dacryopinax spathularia (herein referred to as "AM-1") was studied in male and female Beagle dogs administered AM-1 by oral capsule at doses of 150, 500 or 1000 mg/kg/day for 90 days. AM-1 was well tolerated at all dosages and there were no test article-related effects on survival, clinical observations, neurological screening (functional observational battery) parameters, clinical pathology parameters, organ weights, macroscopic or microscopic evaluations. Test article-related changes were limited to minimal effects on food consumption and body weight changes in the 1000 mg/kg/day group females. Therefore, the no-observed-adverse-effect level (NOAEL) was considered to be 1000 mg/kg/day, the highest dosage level tested. These results add to the safety database for these naturally derived jelly mushroom glycolipids with potential for use as a food ingredient. Highlights: Oral administration of jelly mushroom glycolipids (AM-1) up to 1000 mg/kg/day for 90 days was well tolerated in Beagle dogs. Minimal test-article related effects on food consumption and body weight changes were noted in females given 1000 mg/kg/day. There were no test article-related effects on remaining endpoints and parameters evaluated. The no-observed-adverse-effect level (NOAEL) was considered to be 1000 mg/kg/day, the highest dosage level tested.